PENGARUH AKAD ASURANSI KONVENSIONAL TERHADAP PRINSIP SYARIAH (STUDI KASUS BANK MUAMALAT KOTA BAUBAU) - Amalia Sastia (JISEF : Journal Of International Sharia Economics And Financial, 2022)
This study aims to determine the mechanism of conventional insurance contracts and to determine the level of conformity of conventional insurance contracts with sharia principles. Data collection uses a list of interview guidelines. This research uses descriptive analysis. The results showed that fund management contains elements of usury, gharar, and maysir. There is an element of usury, where compensation payments do not consider the amount of premium paid, and victims or their heirs have the right to receive compensation as a result of traffic accidents. Premiums received are rotated in other interest-free investments, where premiums include mandatory contributions and mandatory contributions. The monthly premium paid by life insurance policyholders is partly a common fund to help members who pass away before the compulsory savings/premium ends. In addition, there is no agreement with the customer that the insurance acts as a fund manager to be invested in other businesses, but the Insurance still acts as a fund manager from participants.